حكاية أبي نواس بين الأدبين االملايوي والعربي : دراسة مقارنة - Najmuddin, Bin Mohamad Said
The story of Abu Nawas is one of the oldest literary tales in the history of Malay Arab Islam, a Persian origin. This story tells about the intelligence of Abu Nawas and his charisma, as well as his charm and his willingness to help people around him. The purpose of this research is to reveal the personality of Abu Nawas and analyze the process of his story as well as to assess the similarity and difference between that story in Arabic literature and its counterpart in Malay literature. This research is based on the French school curriculum, which is based on the relationship of influence and influence between the two literature. This research is based on the personal, comparative and narrative analysis, highlighting the similarities and differences in this story between the Arabic and Malay literature with precision and detail. At the end of the research, the researcher finds that the story of Abu Nawas of ancient Arabia has influenced the story of Abu Nawas Malaya.